Production and Characterization of Compost Macro Nutrients from Mamasa Coffee Waste - Amir, Amir; Purnama, Dirhana; Apindiati, Rita Kurnia (Jurnal Biologi Tropis, 2024)
The higher the productivity of the Mamasa coffee plant, the greater the waste produced and if it is not processed it will cause environmental problems. This research aims to produce and characterize the macro nutrient value in compost from Mamasa coffee waste using the microorganism bioactivator EM 4. This research was carried out by mixing coffee waste with EM-4, water and sugar in certain proportions. The composting process lasts for four weeks, with observations every week to trigger physical and chemical changes in the compost produced. The research results showed that the compost produced had good physical characteristics, namely black in color, not lumpy and odorless. Determination of macro nutrient levels in the organic material of Mamasa coffee waste before and after fermentation into compost showed a significant increase in the macro nutrients it contains, namely total organic C 25.59%; organic matter was 43.91%, Nitrogen was 2.53%, P2O5 was 1.95%, K2O was 1.68%, C/N ratio was 9.48 and water content was 24.34%. Thus, Mamasa coffee waste can be processed into high quality compost using EM-4, thereby providing a sustainable solution for managing organic waste and increasing soil fertility.